Retinitis pigmentaria en paciente masculino de 31 años que presenta disminución visual nocturna. - Muñoz Benítez, Madeline Fabiana (2022)
The present clinical case study deals with a 31-year-old male patient who, due to retinitis pigmentosa, has lost night vision after all the tests carried out, achieving a visual acuity of 20/60, which is corrected with optical aids. Retinitis pigmentosa (RP) comprises a group of degenerative retinal diseases that affect visual field and function. It is characterized by night blindness and loss of. peripheral visual field, and usually has an early and juvenile onset. RP represents the fourth cause of blindness in the world; it has an approximate global prevalence of 1/4,000 and it is estimated that it affects more than 1 million people, it occurs more frequently in men. Retinitis pigmentosa (RP) is an orphan disease that comprises a group of degenerative diseases of the retina. It affects the function and visual field of patients and is characterized by the progressive loss of photoreceptors, especially the rods. It is the most common hereditary degeneration of the retina that causes night blindness and peripheral visual field loss, in addition to other retinal changes, such as pigmentation in bone spicules, waxy pallor of the optic disc, and arteriolar attenuation. The age of onset of these signs and symptoms can vary from childhood to adulthood and their progression varies from patient to patient.